A Pythagorean-Type Fuzzy Deep Denoising Autoencoder for Industrial Accident Early Warning - Zheng, Yu-Jun; Chen, Sheng-Yong; Xue, Yu; Xue, Jin-Yun (IEEE transactions on fuzzy systems, 2017)
Early warning is crucial for preventing industrial accidents and mitigating damage, but current methods are often time-consuming, error-prone, and incompetent to deal with uncertainty. This paper presents a fuzzy deep neural network for early warning of industrial accidents, which equips the classical deep denoising autoencoder (DDAE) model with Pythagorean-type fuzzy parameters in order to enhance the model's representation ability and robustness. To efficiently train the fuzzy deep model, we propose a hybrid algorithm combining Hessian-free optimization and biogeography-based optimization metaheuristic to balance global search and local search. Experiments on datasets from several industrial zones in China show that the proposed Pythagorean-type fuzzy DDAE (PFDDAE) can achieve much higher accuracy of accident risk classification than the classical DDAE and the fuzzy DDAE using regular fuzzy parameters, and the proposed hybrid learning algorithm exhibits significant performance advantage over some other learning algorithms in training PFDDAE. In particular, a test on the 2014 Kunshan aluminum dust explosion accident shows that the deep learning model would be very likely to prevent the accident if it was adopted in advance.